(3KdGKjGJ GdHNGQis - (3eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, CHh YHO Gddg , J (B256 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi NjQ Ndbg eMeO hBdg hUMHg CLeYjf hHYO agPg GdCMGOjK GdKdGKjI ddEeGe GdHNGQi MOjK s
(3BNQgG (B:s
(3MOjK NdGO Hf jMji bGd SeYJ CfS Hf eGdc jbhd CfRdJ BjI GdMLGH ai RjfH HfJ LMT hGWYe YdjgG jheFP NHRkG hdMekG hcGfJ JaJNQ Ydi fSGA GdfHi Udi Gddg Ydjg hSde RhcGfJ Jbhd EfcMfi ai GdSeGA hUdi Gddg Ydi SjOfG eMeO NGJe GdfHjjf hYdi Bdg hUMHg CLeYjfs
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdeLGejYs